Antispasmodics - Kyung Ho Song (Yong Chan Lee, 2022)
Antispasmodics are effective in reducing abdominal pain associated with visceral organs, bloating, and bowel habit changes and are commonly used as "on-demand therapy." A relatively regular intake of antispasmodics may help patients with functional gastrointestinal disease exacerbation. Irritable bowel syndrome and functional dyspepsia are representative functional gastrointestinal diseases with abdominal pain and bloating as the main symptoms. Most of the clinical data on antispasmodics are obtained from studies on functional gastrointestinal diseases including irritable bowel syndrome. Antispasmodics can be safely used for prolonged periods without serious adverse effects; however, different antispasmodics have different anticholinergic potencies. Antispasmodics with strong anticholinergic effects should be prescribed with caution to patients with glaucoma or prostatic hypertrophy-induced dysuria and to those driving vehicles, operating machinery, or receiving other anticholinergic drugs in combination. Antispasmodics meeting US Food and Drug Administration guidelines for efficacy, those showing relatively consistent efficacy in different trials, and those with prokinetic effects are currently available. Many patients with upper gastrointestinal symptoms have overlapping functional gastrointestinal disorders and may require antispasmodic drugs. Alternatively, tricyclic antidepressant or ramosetron use can be considered in patients with irritable bowel syndrome. This review summarizes the clinical data and characteristics of antispasmodics, particularly those available in South Korea.